1988
DOI: 10.1007/bf01535729
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral iron therapy on the upper gastrointestinal tract

Abstract: This study assesses the effect of oral iron therapy on the upper gastrointestinal tract and fecal occult blood testing. Fourteen healthy volunteers completed a checklist of gastrointestinal symptoms, underwent endoscopy and biopsy of the stomach and duodenum, and supplied a fresh stool sample for Hemoccult and HemoQuant testing. They then took ferrous sulfate 325 mg per os tid for two weeks and had the same evaluation repeated. Gastrointestinal symptoms were rated by the patients on a scale of 0-3, endoscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 12 publications
0
17
0
1
Order By: Relevance
“…66 Endoscopy in patients taking oral iron often shows esophageal erosions and gastritis. 67,68 DeLoughery When patients do not respond to oral iron, several factors should be considered. The side effects of stomach pain and constipation can hinder compliance.…”
Section: Treatmentmentioning
confidence: 99%
“…66 Endoscopy in patients taking oral iron often shows esophageal erosions and gastritis. 67,68 DeLoughery When patients do not respond to oral iron, several factors should be considered. The side effects of stomach pain and constipation can hinder compliance.…”
Section: Treatmentmentioning
confidence: 99%
“…12 As the side effects resolve upon cessation of supplementation, there is likely to be no lasting damage to the GI tract. 14 Based on these data, Laine et al have suggested that some symptoms may arise from iron-induced changes in GI motility, 14 so if such changes could be understood, a better supplementation strategy could be devised to reduce side effects and enhance absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Side effects are often poorly managed resulting in patients reducing or stopping iron supplementation . As the side effects resolve upon cessation of supplementation, there is likely to be no lasting damage to the GI tract . Based on these data, Laine et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately orally administered iron compounds, and particularly iron sulphate, the oldest drug used in therapy, may cause irritation and damage to the intestinal mucosa (Laine et al 1988, Hilman 1995.…”
mentioning
confidence: 99%